Attitudes and Preparedness of Lecturers in Supporting Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, Asexual+ (LGBTQIA+) Students: The Role of Training, Policy Knowledge, and Professional Engagement - Remofilwe Sara Makgorog; Constance Matshidiso Lelaka (Universitas Pattimura, 2026)
Lecturers play a pivotal role in fostering inclusive educational environments, but their attitudes and preparedness to support LGBTQIA+ students vary globally. Training in LGBTQIA+ cultural competency enhances awareness of sexual and gender diversity, enabling educators to address student needs while promoting equity, diversity, and social justice. This study explored lecturers’ attitudes and preparedness, focusing on training, policy knowledge, and professional engagement. Six themes emerged: lecturers’ attitudes, collaboration with internal and external stakeholders, importance of LGBTQIA+ training, training received, knowledge of supporting policies, and participation in LGBTQIA+ events. A qualitative exploratory case study design was used, collecting data from ten lecturers through purposive and snowball sampling. Semi-structured interviews were conducted face-to-face and analysed thematically. Findings revealed generally positive attitudes toward LGBTQIA+ students, though concerns about correct pronoun use and misgendering were noted. Most lecturers lacked formal training, relying on self-education, with mixed views on the importance of training due to resource constraints. Awareness of policies and psychosocial support varied, with greater engagement linked to higher knowledge. Participation in LGBTQIA+ events was moderate, while collaboration with stakeholders was identified as key to effective support. The study highlights the critical need for formal training, policy awareness, and structured institutional support to strengthen lecturers’ capacity to support LGBTQIA+ students effectively.